Respuesta :

Answer:

Please check the explanation.

Step-by-step explanation:

Given the expression

5+5(9b - 7)

FIRST CASE (JUST EVALUATION)

Given the expression

[tex]5+5\left(9b-7\right)[/tex]

[tex]\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b-c\right)=ab-ac[/tex]

[tex]5+5\left(9b-7\right)=5+5\cdot \:9b-5\cdot \:7[/tex]

                     [tex]=5+45b-35[/tex]

                     [tex]= 45b - 30[/tex]

Therefore, we conclude that:

[tex]5+5\left(9b-7\right)=45b-30[/tex]

SECOND CASE (Finding the value of b)

Assuming we have to determine the value of b

[tex]5+5(9b - 7) = 0[/tex]

As we have determined

[tex]5+5\left(9b-7\right)=45b-30[/tex]

so substituting [tex]5+5\left(9b-7\right)=45b-30[/tex] in the equation

[tex]45b-30 = 0[/tex]

Add 30 to both sides

[tex]45b-30+30=0+30[/tex]

Simplify

[tex]45b=30[/tex]

Divide both sides by 45

[tex]\frac{45b}{45}=\frac{30}{45}[/tex]

Simplify

[tex]b=\frac{2}{3}[/tex]

Therefore, the value of b = 2/3